Green and efficient synthesis of chiral amines and hydroxylamines by indium (zinc)-copper-mediated alkylation reaction in aqueous media. (24th September 2022) - Feng, Yuqin; Ma, Wenxia; Yang, Ming; Zhang, Gang; Yu, Yunzi; Li, Haibo; Yang, Yongsheng
Abstract: A simple and environmentally friendly method for the alkylation of various chiral nitrones in water using unactivated alkyl halides has been developed. Both the chiral amines and hydroxylamines could be obtained with superior yields and high diastereoselectivity, with a wise choice of different metal complexes. The novelly developed reaction has the characteristics of environmental protection, simple operating, high efficiency, and regioselectivity superbly. Graphical abstract: A simple and environmentally friendly method for the alkylation of various chiral nitrones in water using unactivated alkyl halides has been developed. Both the chiral amines and hydroxylamines could be obtained with superior yields and high diastereoselectivity, with a wise choice of different metal complexes. Different from the previous method, this novelly developed reaction has the characteristics of environmental protection, simple operated, wide range, high efficiency, and regioselectivity superbly. Image 1